2022
DOI: 10.1073/pnas.2024455119
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness is supported by near-critical slow cortical electrodynamics

Abstract: Mounting evidence suggests that during conscious states, the electrodynamics of the cortex are poised near a critical point or phase transition and that this near-critical behavior supports the vast flow of information through cortical networks during conscious states. Here, we empirically identify a mathematically specific critical point near which waking cortical oscillatory dynamics operate, which is known as the edge-of-chaos critical point, or the boundary between stability and chaos. We do so by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
111
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(133 citation statements)
references
References 132 publications
(220 reference statements)
21
111
0
1
Order By: Relevance
“…Cumulatively, our results highlight the urgent need to reconsider analysis of DOC brain activity in light of the diagnostic and prognostic information contained in the traditionally discarded aperiodic EEG component. Our results further support the proposition that the brain of individuals in DOC operates far from a critical point (4), resulting in weaker network susceptibility to global perturbations, such as propofol anesthesia.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Cumulatively, our results highlight the urgent need to reconsider analysis of DOC brain activity in light of the diagnostic and prognostic information contained in the traditionally discarded aperiodic EEG component. Our results further support the proposition that the brain of individuals in DOC operates far from a critical point (4), resulting in weaker network susceptibility to global perturbations, such as propofol anesthesia.…”
Section: Discussionsupporting
confidence: 86%
“…The aperiodic component of the EEG is strongly linked to these measures and has been correlated with signal complexity (20, 35), the perturbation complexity index (10) and the brain’s balance between excitation and inhibition (20). Further, Toker et al (4) demonstrated that the propofol-induced steepening of the spectral slope accompanies the brain’s distancing from criticality. To further investigate the mechanism underlying the change in the aperiodic component, we investigated how the propofol-induced change of the spectral slope was related to alterations in network criticality and complexity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of perceptual content-encoding in the SCP band provides further evidence of the role of SCP in conscious perception, which was previously shown in tasks where the stimulus has poor visibility (Baria et al, 2017) or requires prior knowledge to be recognized (Flounders et al, 2019). A general role of SCP in supporting conscious awareness (He and Raichle, 2009) is also corroborated by recent findings comparing different states of consciousness (Bourdillon et al, 2020;Toker et al, 2022). In the domain of bistable perception, most studies probing neural correlates of perceptual content have employed fMRI [e.g., (Tong et al, 1998;Haynes and Rees, 2005;Wang et al, 2013)], and most electrophysiological studies have focused on changes in ERPs [e.g., (Britz et al, 2009;Pitts et al, 2009)], oscillatory power [e.g., (de Jong et al, 2016)] or neuronal firing rates (Gelbard-Sagiv et al, 2018) around perceptual switches.…”
Section: Discussionsupporting
confidence: 88%
“…The phase transition that occurs within the conscious mammalian brain, according to GRT, is the shift from electrochemical information (synaptic) to electromagnetic field exchanges (ephaptic), the latter of which is significantly faster. This point of criticality supports the vast flow of information during conscious, as opposed to unconscious, states ( Toker et al, 2022 ). As informational speed and bandwidth increase, the depth and scope of the phenomenal consciousness increase.…”
Section: Phase Transitionmentioning
confidence: 56%